2022
DOI: 10.1186/s13018-022-02963-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the fixation ability between lag screw and bone plate for oblique metacarpal shaft fracture

Abstract: Background For oblique metacarpal shaft fracture, if anatomical reduction is achieved through conservative cast immobilization rather than stable fixation, bone malrotation can easily occur, resulting in severe loss in hand prehensile function. However, whether bone plate fixation or only lag screw fixation is more preferable remains unclear. Few studies have evaluated whether screw fixation can provide biomechanical fixation strength similar to bone plate fixation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…For the three fixation methods, the maximum fracture force values were 285.6, 227.8, and 228.2 N, respectively, and the stiffness values were 65.2, 61.7, and 54.9 N/mm, respectively. In addition, Chiu et al [ 25 ] indicated that the use of the lag screw, regular bone plate, and locking plate to fix metacarpal vertical oblique shaft fractures resulted in maximum fracture force values of 153.6, 211.6, and 227.5 N, respectively, and stiffness values of 57.0, 64.7, and 65.4 N/mm, respectively. The findings of the previous study [ 25 ] and those of the current study indicate that the fixation strength of lag screws is not inferior to that of a metallic plate in either horizontal or vertical oblique fractures.…”
Section: Discussionmentioning
confidence: 99%
“…For the three fixation methods, the maximum fracture force values were 285.6, 227.8, and 228.2 N, respectively, and the stiffness values were 65.2, 61.7, and 54.9 N/mm, respectively. In addition, Chiu et al [ 25 ] indicated that the use of the lag screw, regular bone plate, and locking plate to fix metacarpal vertical oblique shaft fractures resulted in maximum fracture force values of 153.6, 211.6, and 227.5 N, respectively, and stiffness values of 57.0, 64.7, and 65.4 N/mm, respectively. The findings of the previous study [ 25 ] and those of the current study indicate that the fixation strength of lag screws is not inferior to that of a metallic plate in either horizontal or vertical oblique fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Metacarpal fracture are a common injury, accounting for 36-42% of hand trauma cases in men aged 18–34 [ 1 ]. The first metacarpal bone is affected in around 25% of all metacarpal fractures, with 80% of those fractures occurring at the base [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%